Kebijakan Program Kampus Mengajar: Antara Cita Pemerintah Dan Realita - Lathifah Irsyadiyah Husna; Farid Setiawan; Yusuf Atma Suryabudi (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2022)
During the pandemic that had an impact on national education, the government organized a teaching campus program as an effort to help schools affected by the pandemic to continue learning. Here the researcher will discuss how the ideals and facts of the campus teach. This research uses a type of library reset research with a descriptive approach. As for the results of this study, the teaching campus has the goal of realizing national goals with students who can contribute to schools. However, in fact there are many obstacles such as pocket money, miscommunication and students having difficulty converting grades.